Re-description of Echiniscus cavagnaroi Schuster & Grigarick, 1966 (Tardigrada: Heterotardigrada: Echiniscoidea: Echiniscidae) from type material, with new records from Hawaii and Bermuda - Meyer, Harry A. (Zootaxa, 2016)
The description of Echiniscus cavagnaroi Schuster & Grigarick, 1966 (Tardigrada: Heterotardigrada: Echiniscoidea: Echiniscidae) is emended with new morphometric measurements of the holotype and eleven paratypes. The length of Cirrus A in the holotype (25.2 μm) was only half the 50 μm reported in the original description. Moreover, the largest values for Cirrus A length and Cirrus A to body length ratio for any specimen (40.6 μm, 21%) were also lower than in the original description. Variation in the presence or absence of spines was considerably greater than originally described. Spines C, Dd and E were not present on all specimens (C present in 67%, Dd in 67%, E in 50%). The length of spines Dd and E, when present, varied greatly among specimens. The geographical range of E. cavagnaroi is expanded by new records from the Hawaiian Islands and Bermuda. The species has been reported from southern China; however, the published description of these specimens differs markedly from type specimens in several respects. The presence of E. cavagnaroi sensu stricto in China needs to be confirmed. The high variability in presence or absence and length of spines in Echiniscus cavagnaroi underscores the importance of assessing variability in these characteristics when identifying unknown specimens or describing new species in the genus. This requires using as many specimens as possible and fully reporting variability.